Correlates of self-paced classes engagement policy & course contents' views by learners at HBMSU, United Arab Emirates. (3rd April 2022) - Awofeso, Niyi; Rabih, Zahour Al Haj
ABSTRACT: One of the core challenges in self-paced online teaching and learning is a decline in learner engagement – the amount, type, and intensity of investments that students make in relation to accessing, reading and learning from materials posted by facilitators during self-paced learning sessions. At Hamdan Bin Mohammed Smart University (HBMSU), Dubai, United Arab Emirates, a policy of mandating assessment of engagement with self-paced classes was trialled between 2016 and 2017, with penalties ranging from loss of 0.5 mark per class to dismissal from courses for four failed self-paced assignment assessments. The policy led to significant access to course materials by learners taking two analysed health courses compared with engagement with self-paced classes in the same courses prior to introduction of the policy. Only 10 of 57 students accessed all posted learning materials during the review period. However, there was no significant difference in the performance by a minority of learners who consistently accessed all study materials in self-paced weeks compared with learners who selectively accessed some of the course materials during self-paced weeks. A survey of the minority group of 10 learners who accessed all learning materials revealed important insights on the facilitators and impediments to self-study for engaged learning.